2016
DOI: 10.1016/j.physe.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Hopping magnetoresistance in ion irradiated monolayer graphene

Abstract: Magnetoresistance (MR) of ion irradiated monolayer graphene samples with variable-range hopping (VRH) mechanism of conductivity was measured at temperatures down to $T = 1.8$ K in magnetic fields up to $B = 8$ T. It was observed that in perpendicular magnetic fields, hopping resistivity $R$ decreases, which corresponds to negative MR (NMR), while parallel magnetic field results in positive MR (PMR) at low temperatures. NMR is explained on the basis of the "orbital" model in which perpendicular magnetic field s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
(52 reference statements)
1
11
1
Order By: Relevance
“…In our experiments [17][18][19], large-sized MG specimens 10x10 mm and 5x5 mm were supplied by the "Graphenea" Co. In accordance with certificate, monolayer graphene was produced by CVD method on copper catalyst and transferred to a 300 nm SiO2/Si substrate using a wet transfer process.…”
Section: Samples and Irradiationmentioning
confidence: 99%
“…In our experiments [17][18][19], large-sized MG specimens 10x10 mm and 5x5 mm were supplied by the "Graphenea" Co. In accordance with certificate, monolayer graphene was produced by CVD method on copper catalyst and transferred to a 300 nm SiO2/Si substrate using a wet transfer process.…”
Section: Samples and Irradiationmentioning
confidence: 99%
“…10,11 . It was shown that σ(T ) for sample 1 with a low density of defects, N D , is accurately described in the framework of the weak localization (WL) model, whereby σ(T ) ∼ ln(T ) and saturates at low T .…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…In spite of extensive research into the galvanomagnetic properties of graphene layers and graphene/metal hybrid structures, there is still one more problem concerning understanding the main electrotransport mechanisms in graphene. Most of this research has dealt with micron sized graphene specimens produced either by debonding from graphite [12,[15][16][17][18] or cutting from single polycrystalline graphene grains [19][20][21]. However carrier transport in magnetic fields for large specimens (millimeters or fractions of a millimeter) has been dealt with in only a few works [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…For strong localization one has to give preference to a hopping conductivity mechanism obeying the Mott [28] or Shklovsky-Efros [29] models for a zero magnetic field or the Mikoshiba [30] or Altshuler-Aronov-Khmelnitsky [27] models for electrotransport in an external magnetic field. Medium localization (between weak and strong) requires both interference and hopping transport mechanisms be taken into account [19][20][21]. Metallic particles (islands) deposited onto composite structures containing graphene layers may form spatially distributed (defragmented) metallic bridges [14,31] which can bend current paths in graphene layers in a transverse magnetic field (through the effect of Lorentz force) and trigger the contribution of extraordinary magnetoresistance effect to magnetotransport [32].…”
Section: Introductionmentioning
confidence: 99%